Dowry Practice among Madheshi Community of Dhanusha District of Nepal Continuity and Change - Yadav, Leelawati (Pragya Darshan प्रज्ञा दर्शन, 2023)
Dowry system is a burning issue in the Nepalese and Indian society. In Nepal, dowry practice is more prevalent in the Tarai region in the border areas between Nepal and India. Dowry practice has been found mostly in higher caste and higher educated family of Madheshi people. Among them Yadav and Sah Caste has its higher and higher practices. They have been found to giving continuity of dowry to main social prestige and can't leave the social cultures that have strongly rooted in Madheshi community. It is difficult and bad situation of Tarai in regards of women violence that is directly and indirectly interlinked with dowry practice. So in this article I argued that practice of dowry is increasing day by day but the cases are in hidden way. Based on key informants this study highly demands for removing of this dowry practice from Tarai. It is needed of further research activity, effective formulation and implementation of government Laws & Policies and to punish those who are directly and indirectly involved in giving and taking dowry. Thus way it is expected that the life of young married girls could be saved in the Tarai region of Nepal, particularly in my study area.